Effect of urosodeoxycholic acid therapy on lymphocyte function of patients with primary biliary cirrhosis - OGINO, Hedero; KAWAI, Hiroshi; KOBAYASHI, Kenichi; KANEKO, Shuichi; TERASAKI, Shuichi; MATSUSHITA, Eiki; URABE, Takeshi; UNOURA, Masashi; NAKANUMA, Yasuni; YANAGI, Masayuki (Kanzo, 1993)
Primary biliary cirrhosis (PBC) is a chronic autoimmune liver disease. In order to elucidate the role of urosodeoxycholic acid (UDCA) treatment through immune reaction, we studied lymphocyte function of patients with primary biliary cirrhosis with or without UDCA treatment. 28 patients with asymptomatic PBC (21 treated and 7 non-treated with UDCA (600mg/day, p.o.)) and 7 normal subjects were studied. 5 patients were evaluated before and after treatment with UDCA. In T cell subsets, the ratio of CD3 positive cell was low in patients treated with UDCA compared to that in patients without UDCA treatment (p<0.05). Although no significant difference among three groups was shown in the lymphocyte stimulation tests, the natural killer cell activity was significantly high and the interleukin 2 production was significantly low in patients treated with UDCA compared with those in patients without UDCA treatment (p<0.05). In vitro study, the natural killer cell activity became significantly low when peripheral blood mononuclear cells (PBMCs) were incubated with 1.0, 00.0 or 100.0μM of chenodeoxycholic acid (CDCA). However, the effect of CDCA on the natural killer cell activity was diminished when PBMCs were incubated with UDCA simultaneously. Thus, these data suggest that the effect of UDCA treatment for patients with PBC may be mediated through immune reaction induced by the change of bile acid composition.